Mrs. Roy Chittick breaks open a pinata - Martin & Rita Rowe (photographic studio):::Creator::::::::::::
Photograph shows Mrs. Roy Chittick breaking open a Christmas tree pinata with a wooden dowel on December 18, 1963. A group of small children and a few women are watching. Mrs. Alfred Abram is wearing a checkered two piece outfit and is standing in the background on the far right.